MtSUPERMAN plays a key role in compound inflorescence and flower development in Medicago truncatula. (9th December 2020) - Rodas, Ana L.; Roque, Edelín; Hamza, Rim; Gómez‐Mena, Concepción; Minguet, Eugenio G.; Wen, Jiangqi; Mysore, Kirankumar S.; Beltrán, José P.; Cañas, Luis A.
SUMMARY: Legumes have unique features, such as compound inflorescences and a complex floral ontogeny. Thus, the study of regulatory genes in these species during inflorescence and floral development is essential to understand their role in the evolutionary origin of developmental novelties. The SUPERMAN ( SUP ) gene encodes a C2H2 zinc‐finger transcriptional repressor that regulates the floral organ number in the third and fourth floral whorls of Arabidopsis thaliana . In this work, we present the functional characterization of the Medicago truncatula SUPERMAN ( MtSUP ) gene based on gene expression analysis, complementation and overexpression assays, and reverse genetic approaches. Our findings provide evidence that MtSUP is the orthologous gene of SUP in M. truncatula . We have unveiled novel functions for a SUP ‐like gene in eudicots. MtSUP controls not only the number of floral organs in the inner two whorls, but also in the second whorl of the flower. Furthermore, MtSUP regulates the activity of the secondary inflorescence meristem, thus controlling the number of flowers produced. Our work provides insight into the regulatory network behind the compound inflorescence and flower development in this angiosperm family. Significance Statement: MtSUPERMAN ( MtSUP ) is the orthologue of the SUPERMAN gene of Arabidopsis in the model legume Medicago truncatula . MtSUP is the first gene identified that controls the number of flowers in the compound inflorescence in a legume species, being a novel function for a SUPERMAN orthologue in eudicots.